Israeli Musicians as National Representatives - Pánek Jurková, Jitka (Lidé města, 2015)
This paper researches how Israeli musicians represent their nation during performances for a foreign audience. It claims that a nation is not always portrayed as a homogenous entity; rather, the musicians relate in various ways to different “imagined communities” (Anderson 1991) through their performances. These strategies are traceable by the musicians’ verbal statements, visual markers, and music. The paper proposes four such strategies.